TAUHID EDUCATION IN PESANTREN (Study of Tauhid Thought and Education in Pesantren al-Mukmin Ngruki, Central Java, Indonesia) - Zakariya, Din Muhammad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
AbstractThis research aims to reveal the thoughts possessed by the kyais and ustadzin Pesantren al-Mukmin on the tauhÃ®d education, and their implementation.The method used in this reseach was qualitative. The results of this researchare as follows. Firstly, tauhÃ®d is given a special attention since the main aimof education in the pesantren al-Mukmin Ngruki is to produce a muslimgeneration with pure tauhÃ®d coloring all their lives. KH. Wahyudin and ustadzAbdurrahim Baâasyir Lc understand tauhÃ®d in line with Ibnu Taimiyah andMuhammad bin Abdul Wahab. Secondly, TauhÃ®d education in Pesantren al-Mukmin Ngruki using three methods of education; the doctrine of tauhÃ®dvalues, understanding, and practice. Meanwhile the learning of tauhÃ®d in thePesantren al-Mukmin Ngruki more adopted the concept of tauhÃ®d proposedby Muhammad bin Abdul Wahab and Ibn Taimiyah since the books studiedin the halaqah program are written by Muhammad bin Abdul Wahab, whilethose studied in the learning of tauhÃ®d in the class are written by Dr. ShalihFauzan who is one of the figures in the Muhammad bin Abdul Wahab tauhÃ®ddakwah movement in Saudi Arabia.Â Keywords: TauhÃ®d, Education, Pesantren